Non closure of parietal peritoneum at cesarean section and adhesion formation - Choudhary, Anjali; Bansal, Neeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Cesarean section is the most commonly performed surgery worldwide. Recent times have seen rising trends in c-section rates, for a variety of reasons. Although the basic procedure remains same, some new techniques have been adopted like not closing the visceral or the parietal peritoneum. A large number of studies on merits and demerits of these practices have been published, generating even larger debates. Objective of this effort is to evaluate studies on either side of the argument and cite our experiences. Methods: Repeat cesarean sections were evaluated for adhesion related procedural problems in both peritoneal closure and non closure in primary cesareans. Results: Dense adhesions were observed in cases where peritoneal closure was not done in previous surgery and there were fewer or less dense adhesion cases where routine closure of parietal peritoneum was practiced. Conclusion: Routine closure of parietal peritoneum in cesarean sections is recommended to reduce adhesion related morbidity and difficult subsequent surgery.